2012
DOI: 10.1002/ccd.24310
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of 7F sheathless guiding catheter during transradial coronary intervention

Abstract: In our multicenter study of 116 consecutive patients, using 7F sheathless guiding catheter to perform TRI is associated with a high procedural success (95%) and a low 30-day RAO rate (2.5%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 14 publications
(20 reference statements)
1
28
0
1
Order By: Relevance
“…Surprisingly, the sheathless guide catheter could enter the radial artery in a smooth and pain‐free manner and postprocedural Doppler ultrasound of the radial artery was unremarkable. This is in line with previous reports on the feasibility of inserting a 7 Fr guide catheter over a 5 Fr diagnostic catheter as a “modified” sheathless technique . Therefore, we can assume that standard nonhydrophilic guide catheters could also offer a solution to remove kinked catheters.…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, the sheathless guide catheter could enter the radial artery in a smooth and pain‐free manner and postprocedural Doppler ultrasound of the radial artery was unremarkable. This is in line with previous reports on the feasibility of inserting a 7 Fr guide catheter over a 5 Fr diagnostic catheter as a “modified” sheathless technique . Therefore, we can assume that standard nonhydrophilic guide catheters could also offer a solution to remove kinked catheters.…”
Section: Discussionsupporting
confidence: 90%
“…The reported rate of radial artery occlusion in patients undergoing sheathless TRA for complex coronary artery disease was 2.5% 16 ; additionally, the study also suggested that elevated serum creatinine and peripheral artery occlusion were more likely to be associated with radial artery occlusion when using a 7-F sheathless approach. 16 In our study of the sheathless TRA technique in chronically occluded coronary arteries, the incidence of radial artery occlusion was 4.2% at 1 year. 17 In the current study of the sheathless TRA for CAS, the duplex-documented rate was 9%, probably related to more device manipulation during the procedure.…”
Section: Discussionmentioning
confidence: 96%
“…We have used standard available equipment to fashion an inner dilator for standard guide catheter and prepared a modified mother‐and‐child system, which should help preventing RA injury, perforation, hematoma and local pain by eliminating “razor effect” . We have also used a 7F introducer sheath with its minimal entry inside the RA lumen to create a virtual sheathless guide system which should help reducing RA spasm and RA occlusion by minimizing the segment of mis‐match between RA and introducer sheath . Outer diameters (OD) of 7F guide catheters from different manufacturers i.e.…”
Section: Discussionmentioning
confidence: 99%